Why India is not a Great Power (yet) - Karnad, Bharat (Oxford Univwesity Press, 2015)
Since the economic liberalization of the early 1990s, India has been, on several occasions and at different forums, feted as a great power. This subject has been discussed in numerous books, but mostly in terms of rapid economic growth and immense potential in the emerging market. There is also a vast collection of literature on India's 'soft power '- culture, tourism, frugal engineering, and knowledge economy. However, there has been no serious exploration of the alternative path India can take to achieving great power status - a combination of hard power, geostrategics, and realpolitik.